2010
DOI: 10.1371/journal.pone.0009419
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate DNA in Fecal Samples from Bonobos and Gorillas: Evidence for Meat Consumption or Artefact?

Abstract: BackgroundDeciphering the behavioral repertoire of great apes is a challenge for several reasons. First, due to their elusive behavior in dense forest environments, great ape populations are often difficult to observe. Second, members of the genus Pan are known to display a great variety in their behavioral repertoire; thus, observations from one population are not necessarily representative for other populations. For example, bonobos (Pan paniscus) are generally believed to consume almost no vertebrate prey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…2), which is the taxonomic group containing the highest overall representation of gamma-ERVs. It may be possible that these euarchontoglire hosts are not strictly vegetarian because recent studies suggest that several of these taxa do occasionally eat meat (22,23), given that even rare carnivorous acts may be sufficient to expose hosts to retroviral infection. Other life-history and ecological traits may also influence susceptibility to infection by gammaretroviruses.…”
Section: Significancementioning
confidence: 99%
“…2), which is the taxonomic group containing the highest overall representation of gamma-ERVs. It may be possible that these euarchontoglire hosts are not strictly vegetarian because recent studies suggest that several of these taxa do occasionally eat meat (22,23), given that even rare carnivorous acts may be sufficient to expose hosts to retroviral infection. Other life-history and ecological traits may also influence susceptibility to infection by gammaretroviruses.…”
Section: Significancementioning
confidence: 99%
“…Humans have a long history of meat consumption, although our closest primate relatives are vegetarian (Gorilla gorilla) or low, but clearly not zero, meat consumers (Pan troglodytes and Pan paniscus) (Nishida and Uehara, 1983;Stanford, 1996;Hofreiter et al, 2010). Further, there is good evidence that some of our hominin cousins (Australopithecus bahrelghazali, Paranthropus robustus and Australopithecus sediba) were largely plant eaters (Balter et al, 2012;Henry et al, 2012a;Lee-Thorp et al, 2012).…”
Section: Meatmentioning
confidence: 99%
“…Gorillas have never been observed to hunt, nor have remains of prey been observed in their feces. A first molecular study of gorilla diet, also in Loango, identified mammal DNA sequences in their feces [Hofreiter et al, 2010]. The authors carefully discussed this finding and mentioned the possibility of environmental or laboratory contamination.…”
Section: Study Populations and Sample Collectionmentioning
confidence: 99%
“…Measuring the frequency of hunting through direct observations is possible but only where great apes have been habituated [Boesch and Boesch-Achermann, 2000]; and to our knowledge, parasite nucleic acid persistence through the digestive tract of great apes has never been assessed (whatever the parasite). By means of molecular tools, it is possible to screen fecal samples for prey DNA [Symondson, 2002], as previously done to study the diet of great apes [Hofreiter et al, 2010] and many other predators [O'Rorke et al, 2012]. Here, we use molecular methods to detect prey DNA in fecal samplings of two distinct chimpanzee communities, using fecal samples of western lowland gorillas as negative control (as they are not carnivorous), to assess to what extent this is prevalent ("prey prevalence") and could effectively pose a risk of false interpretation in fecal epidemiology studies.…”
Section: Introductionmentioning
confidence: 99%